Kajian Takhrij Al-Hadis dan Filosofis Terhadap Hadis tentang Kejujuran Membawa Kepada Kebaikan - Adinda Aisyah Nurussyifa; Arifuddin Ahmad (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Honesty is a fundamental value in Islamic teachings that is closely related to the formation of individual morality and social order. One hadith that explicitly emphasizes the importance of honesty is the saying of the Prophet Muhammad (peace be upon him), which states that honesty leads to goodness and goodness leads to Paradise. This study aims to examine the hadith on honesty through the approach of takhrij al-?adith and philosophical analysis in order to determine its authenticity, textual variations, and the ethical implications of its meaning in the social life of Muslims. This research employs a qualitative method with a library research design. Primary data sources consist of authoritative hadith collections such as ?a?i? al-Bukhari, ?a?i? Muslim, Sunan Abu Dawud, Sunan al-Tirmidhi, and Musnad A?mad, supported by secondary sources including scholarly books and academic journal articles. Data analysis was conducted through the stages of hadith tracing (takhrij), sanad and matn criticism, itibar of transmission chains, as well as philosophical and contextual analysis. The findings indicate that the hadith stating that “honesty leads to goodness” has a continuous chain of transmission, reliable narrators (thiqah), and a text that does not contradict the Qur’an or sound reasoning, thus classifying it as an authentic hadith. Philosophically, this hadith affirms that honesty serves as a foundational principle for moral integrity, noble character development, and social harmony, while dishonesty constitutes a source of moral and social corruption. Therefore, the internalization of honesty as taught in the hadith remains highly relevant in addressing contemporary moral challenges.